Fatal SARS-CoV-2 and Mycobacterium tuberculosis coinfection in an infant: insights from Botswana. Issue 4 (21st April 2021) - Mulale, Unami Koolebogile; Kashamba, Thanolo; Strysko, Jonathan; Kyokunda, Lynnette Tumwine
Abstract : We report a fatal case of SARS-CoV-2 and Mycobacterium tuberculosis coinfection in an infant, Botswana's first paediatric COVID-19-associated fatality. The patient, a 3-month-old HIV-unexposed boy, presented with fever and respiratory distress in the setting of failure to thrive. Both the patient and his mother tested positive for rifampin-sensitive M. tuberculosis (Xpert MTB/Rif) and SARS-CoV-2 (real time-PCR). Initially stable on supplemental oxygen and antitubercular therapy, the patient experienced precipitous clinical decline 5 days after presentation and subsequently died. Autopsy identified evidence of disseminated tuberculosis (TB) as well as histopathological findings similar to those described in recent reports of SARS-CoV-2 infections, including diffuse microthrombosis. TB remains a serious public health threat in hyperendemic regions like sub-Saharan Africa, and is often diagnosed late in infants. In addition to raising the question of additive/synergistic pathophysiology and/or immune reconstitution, this case of coinfection also highlights the importance of leveraging the COVID-19 pandemic response to strengthen efforts for TB prevention, screening and detection.